Pengaruh Corporate Social Responsibility Dan Good Corporate Governance (Studi kasus pada Perusahaan Manufaktur Subsektor Tekstil & Garment tahun 2019-2022) - Dhara Meuthya Deni; Rahmaita (Jurnal Akuntansi Keuangan dan Bisnis, 2024)
This study aims to examine the effect of Corporate Social Responsibility on financial performance listed on the Indonesia Stock Exchange in 2019-2022. This research uses a quantitative descriptive approach. The data used is secondary data from financial reports and sustainability reports of Textile & Garment subsector manufacturing companies listed on the Indonesia Stock Exchange. The type of research used is explanatory research using explanatory research quantitative data. The sampling technique in this study uses the time series method used is purposive sampling method, the sample and this research are 13 manufacturing companies in the Textile & Garment subsector. The results of this study Corporate Social Responsibility has a positive effect on partial financial performance in textile and garment sub-sector manufacturing companies listed on the Indonesia Stock Exchange for the 2019-2022 period, Managerial Ownership has a positive effect on partial financial performance, there is a positive influence between the Independent Board of Commissioners on partial financial performance, the Audit Committee has a negative effect on financial performance in textile and garment sub-sector manufacturing companies listed on the Indonesia Stock Exchange for the 2019-2022 period.